Предмет: Математика,
автор: Shadow007
Упростить выражение (4m-3)/(m-2) + (2m+1)/(2-m)
Приложения:
Ответы
Автор ответа:
0
4m-3 2m+1 4m-3-2m-1 2m-4 2(m-2)
= ---------- - ---------- = ---------------- = ---------- = ---------- = 2
m-2 m-2 m-2 m-2 m-2
= ---------- - ---------- = ---------------- = ---------- = ---------- = 2
m-2 m-2 m-2 m-2 m-2
Похожие вопросы
Предмет: Обществознание,
автор: lisakapustina04
Предмет: Английский язык,
автор: kayrat2122
Предмет: Қазақ тiлi,
автор: ostroverkhovaelizave
Предмет: Математика,
автор: 555МИЛА
Предмет: Математика,
автор: nelli197701